B Cell Recognition of Candida albicans Hyphae via TLR 2 Promotes IgG1 and IL-6 Secretion for TH17 Differentiation - Ferreira-Gomes, Marta; Wich, Melissa; Böde, Sally; Hube, Bernhard; Jacobsen, Ilse D.; Jungnickel, Berit (Frontiers in Immunology, 2021)
Candida albicans is usually a benign member of the human gut microbiota, but can become pathogenic under certain circumstances, for example in an immunocompromised host. The innate immune system, in particular neutrophils and macrophages, constitutes a crucial first line of defense against fungal invasion, however adaptive immunity may provide long term protection and thus allow vaccination of at risk patients. While TH1 and TH17 cells are important for antifungal responses, the role of B cells and antibodies in protection from C. albicans infection is less well defined. In this study, we show that C. albicans hyphae but not yeast, as well as fungal cell wall components, directly activate B cells via MyD88 signalling triggered by Toll- like receptor 2, leading to increased IgG1 production. While Dectin-1 signals and specific recognition by the B cell receptor are dispensable for B cell activation in this system, TLR2/MyD88 signals cooperate with CD40 signals in promoting B cell activation. Importantly, recognition of C. albicans via MyD88 signalling is also essential for induction of IL-6 secretion by B cells, which promotes TH17 polarization in T-B cell coculture experiments. B cells may thus be activated directly by C. albicans in its invasive form, leading to production of antibodies and T cell help for fungal clearance.